On the relationship between reversal of the river stage (repiquetes), rainfall and low-level wind regimes over the western Amazon basin - Figueroa M. (2020)
Study region: The Amazonas River and its tributaries (Peru), where riparian farmers face hydrological events that put their lowland crops at high risk of production loss during the flood recession period. Study focus: This paper analyzes the hydro-meteorological mechanisms over the Andes-Amazon basins that produce “repiquetes”, which are sudden reversals of the river stage. They are defined and characterized for the period 1996–2018 by using river stage data from three hydrological gauging stations for the Amazonas, Marañón and Ucayali Rivers. Daily rainfall and low-level winds depict the large-scale atmospheric patterns associated with repiquetes. New hydrological insights: Among 73 significant repiquetes (reversal ? 20 cm) observed in the Amazonas River, 64 % were preceded by repiquetes only in the Marañón River, 5 % by repiquetes only in the Ucayali River, 21 % by repiquetes in both rivers and 10 % was only registered in the Amazonas River without upstream precursor. These results show that repiquetes in the Marañón River are the primary precursors of repiquetes in the Amazonas River. Most repiquetes are associated with abundant rainfall over the Peruvian and Ecuadorian Andes-Amazon transition region related to a remarkable change in the direction of the meridional wind, from north to south, and an easterly flow five to three days before the beginning of a repiquete in the Amazonas River. © 2020